Release characteristics of blends from slow, controlled and conventional nitrogen fertilizers and uptake by corn - Andrade, André Baldansi (2016)
Slow release fertilizers (SRF) and controlled release fertilizers (CRF) may improve nitrogen (N) use efficiency by crops, but their high costs are impeditive for widespread use. An alternative for that is the mixing of conventional fertilizer with SRF or CRF. The aim of this work was to assess the capacity of N sources in feed a corn crop in a pot experiment and to determine N release curves by polymer coated ureas at different aqueous mediums, by varying pH and ionic strength. The experiment was carried out under a greenhouse condition in pots filled with oxisol. The experimental design was a completely randomized factorial 14 x 4, with three repetitions. Treatments consisted of granular urea, ammonium nitrate, polymer coated ureas (multicote 4M ® , urea + plastic resin and urea + polyurethane), urea formaldehyde and the mixing of CRF/SRF with granular urea (ratio of 40:60 in % of N and vice versa) in the rates of 0, 150, 300 and 450 mg N kg -1 . Three corn croppings were conducted, and at the end of each cropping, we evaluated nitrogen content, dry mass, nitrogen accumulation, SPAD index, agronomic efficiency index (AEI) and applied nitrogen recovery (ANR) in corn shoots after each cropping. The results varied widely among treatments given the wide range of N release capacity of the sources. For cumulative (sum of three croppings) dry mass, the order followed ammonium nitrate = M60:U40 = A40:U60 = urea + polyurethane > granular urea = multicote 4M ® = M40:U60 = urea + plastic resin = A60:U40 = B40:U60 = B60:U40 = C40:U60 > urea formaldehyde = C60:U40. For cumulative N accumulation, the order followed ammonium nitrate > granular urea = urea + polyurethane = C40:U60 > M40:U60 = A40:U60 = A60:U40 = B40:U60 > multicote 4M ® = M60:U40 = urea + plastic resin = B60:U40 > C60:U40 > urea formaldehyde. For the N release test, different aqueous mediums did not cause differences in N release at most of the days analysed. The use of blends is a promising option against high costs of CRF or SRF.